Analysis of treatment outcomes in patients with progressive locally advanced non-resectable and disseminated medullary thyroid cancer receiving vandetanib outside of clinical trials (Russian experience) - I. S. Romanov; А. М. Mudunov; S. О. Podvyaznikov; А. V. Ignatova; Yu. V. Alymov (Опухоли головы и шеи)
The study objective is to perform retrospective analysis of the efficacy and safety of vandetanib for metastatic and non-resectable medullary thyroid cancer in routine clinical practice. Materials and methods. We analyzed treatment outcomes in 46 patients treated with vandetanib. We also evaluated progression-free survival, overall survival, time to progression, and frequency of adverse events. Results. At a median follow-up time of 27.4 months (range: 2.5–106.5 months) and median duration of vandetanib therapy of 21 months, disease progression was registered in 32.6 % of cases, whereas stable disease was observed in 28.3 % of cases and 8.7 % of study participants demonstrated partial response. One patient had complete response to treatment. Almost one-third of patients (28.2 %) died, including 2 individuals whose death was not associated with cancer. The one-year and three-year progression-free survival rates were 67.3 % and 33.3 %, respectively; the two-year and five-year overall survival rates were 82.4 % and 29.4 %, respectively. The efficacy of therapy was confirmed by a 79.4 % decrease in the serum level of calcitonin after treatment initiation. Side effects were observed in 33.9 % of patients (primarily skin and gastrointestinal toxic reactions) and were easily managed in most of the cases. Eight individuals (17.4 %) required cessation of vandetanib due to adverse events. Conclusion. Our findings suggest high efficacy and acceptable safety profile of vandetanib in the treatment of progressive locally advanced non-resectable and disseminated medullary thyroid cancer